2012
DOI: 10.1002/jbmr.1548
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-terminal kinase 1 negatively regulates osteoblastic differentiation induced by BMP2 via phosphorylation of Runx2 at Ser104

Abstract: Runx2 plays a crucial role in osteoblastic differentiation, which can be upregulated by bone morphogenetic proteins 2 (BMP2). Mitogenactivated protein kinase (MAPK) cascades, such as extracellular signal-regulated kinase (ERK) and p38, have been reported to be activated by BMP2 to increase Runx2 activity. The role of cjun-N-terminal kinase (JNK), the other kinase of MAPK, in osteoblastic differentiation has not been well elucidated. In this study, we first showed that JNK1 is activated by BMP2 in multipotent C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 53 publications
5
47
0
1
Order By: Relevance
“…Furthermore, a recent study showing that inhibition of GSK3␤ leads to attenuation of MP-induced bone loss in rats (46) further supports our finding that active GSK3␤-mediated Runx2 phosphorylation is apparently involved in its degradation by Fbw7, leading to bone loss. Although there are few studies demonstrating phosphorylation of Runx2 affecting its protein stability, none of them addressed the E3 ubiquitin ligase involved in such regulation (15,25). Our data demonstrating Runx2, GSK3␤, and Fbw7 to physically interact with each other in osteoblasts is again in agreement with previous findings that suggest physiological interaction of GSK3␤ with Runx2 is required for attenuating Runx2 functions (25).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, a recent study showing that inhibition of GSK3␤ leads to attenuation of MP-induced bone loss in rats (46) further supports our finding that active GSK3␤-mediated Runx2 phosphorylation is apparently involved in its degradation by Fbw7, leading to bone loss. Although there are few studies demonstrating phosphorylation of Runx2 affecting its protein stability, none of them addressed the E3 ubiquitin ligase involved in such regulation (15,25). Our data demonstrating Runx2, GSK3␤, and Fbw7 to physically interact with each other in osteoblasts is again in agreement with previous findings that suggest physiological interaction of GSK3␤ with Runx2 is required for attenuating Runx2 functions (25).…”
Section: Discussionsupporting
confidence: 82%
“…In osteoblasts, Runx2 levels are regulated coordinately with the cell cycle machinery, apparently by E3 ubiquitin ligases (14,24). Runx2 expression in osteoblasts is also down-regulated upon its phosphorylation by GSK3␤ (25) and JNK1 (15) ligase for Runx2 based on following evidence: (a) phosphorylation of Runx2 negatively regulates its activity (13,15,25); (b) GSK3␤ negatively regulates osteogenesis by phosphorylating Runx2 and inhibiting its activity (25); (c) insulin signaling-mediatedPI3K/AKTpathwaypromotesosteogenesiswithoutphosphorylating Runx2 (26,27); and (d) there are several putative CPD motifs within Runx2 protein, and some of these CPDs also harbor GSK3␤ consensus phosphorylation motifs known to be phospho-modified by GSK3␤ (25). Here, we studied whether Fbw7␣ serves as an E3 ubiquitin ligase for Runx2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the Smad1/5/8 transcription factors, MAPKs are also involved in BMPs osteogenic signaling transduction (11-14). Recently, we have reported that p38 and ERK1/2 MAPKs act in opposition to regulate BMP9-induced osteogenic differentiation of MSCs (15).…”
Section: Discussionmentioning
confidence: 99%
“…The classic BMPs signaling pathway operates by activation of the transcription factors Smads (2,10), and there are growing evidences that it can also act through a Smads-independent mitogen activated protein kinases (MAPKs) signaling pathway (2,11-14). Our recent study has demonstrated that p38 and ERK1/2, two subfamilies of MAPKs, play important roles in regulating BMP9-induced osteogenic differentiation of MSCs (15).…”
Section: Introductionmentioning
confidence: 99%